2016
DOI: 10.1038/mp.2016.74
|View full text |Cite|
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder in adults: A systematic review and meta-analysis of genetic, pharmacogenetic and biochemical studies

Abstract: The adult form of attention-deficit/hyperactivity disorder has a prevalence of up to 5% and is the most severe long-term outcome of this common disorder. Family studies in clinical samples as well as twin studies suggest a familial liability and consequently different genes were investigated in association studies. Pharmacotherapy with methylphenidate (MPH) seems to be the first-line treatment of choice in adults with attention-deficit hyperactive disorder (ADHD) and some studies were conducted on the genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(139 citation statements)
references
References 143 publications
(252 reference statements)
5
129
2
3
Order By: Relevance
“…The prevalence of ADHD symptoms status among drug dependent patients was significantly higher in comparison with the rate of adult ADHD diagnosis in the general population reported in previous research (5.0%) (Bonvicini et al, 2016). Similarly, adult ADHD was found to be over-represented by other research groups in SUD populations and, subject to the sampling methodology applied, prevalence was reported to range from 14% to 44% (McAweeney et al, 2010Van de Glind et al, 2014), which is considerably higher than the rate observed in the community (Kessler et al, 2006), in particular the 2.9% and 4.4% reported in the United States (Faraone and Biederman, 2005; Kessler et al, 2006) and the 5.29%, 2.5% world-wide (Polanczyk et al, 2007; Simon et al, 2009).…”
Section: Discussioncontrasting
confidence: 65%
“…The prevalence of ADHD symptoms status among drug dependent patients was significantly higher in comparison with the rate of adult ADHD diagnosis in the general population reported in previous research (5.0%) (Bonvicini et al, 2016). Similarly, adult ADHD was found to be over-represented by other research groups in SUD populations and, subject to the sampling methodology applied, prevalence was reported to range from 14% to 44% (McAweeney et al, 2010Van de Glind et al, 2014), which is considerably higher than the rate observed in the community (Kessler et al, 2006), in particular the 2.9% and 4.4% reported in the United States (Faraone and Biederman, 2005; Kessler et al, 2006) and the 5.29%, 2.5% world-wide (Polanczyk et al, 2007; Simon et al, 2009).…”
Section: Discussioncontrasting
confidence: 65%
“…BAIAP2 is involved in neuronal proliferation, survival, and maturation and dendritic spine morphogenesis and may affect neuronal growth-cone guidance. These findings were significant even after Bonferroni correction [73]. For both the child and adult meta-analyses, the strength of each association, as measured by the odds ratio, is small, less than 1.5.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 81%
“…As a result, the half-life of atomoxetine ranges from 5.2 h in rapid metabolizers to 21.6 h in slow metabolizers [145]. Some work has looked into CES1 variants regarding the regulation of methylphenidate metabolism and CYP2D6/ CYP3A4 variants and the metabolism of ADHD, but the evidence base has not generated consistent results for either children [146] or adults [73].…”
Section: Pharmacogenetics Of Adhdmentioning
confidence: 99%
“…Canonical ADHD-associated hyperactivity should be alleviated by methylphenidate, a psychostimulant that increases dopamine release and is routinely used to treat ADHD (32,33). Surprisingly, the hyperactivity of the Ndrg2 -/-mice was not effectively suppressed by methylphenidate treatment (Supplemental Figure 9), suggesting that a unique neurobiological mechanism mediates NDRG2 deficiency-induced hyperactivity.…”
Section: Hyperactivity In Ndrg2mentioning
confidence: 99%